Evidence and Ideology on Consumer Choices in Education Markets - Christopher Lubienski; Gregg Garn (Arizona State University, 2010)
The question of how information is used by parents in selecting schools is a central issue in school choice debates, where advocates and opponents frequently intermingle theory (often economic), ideological beliefs, and empirical evidence in constructing arguments about the potential of this reform. We employ a nomination strategy to analyze rational choice claims about information on school quality, finding a much more complex picture of this issue than is typically found in policy advocacy. We offer an alternative framework for evaluating consumer information on schools, concluding that researchers and policymakers must consider the nature, quality, and equitable distribution of information.